2013
DOI: 10.1136/injuryprev-2012-040689
|View full text |Cite
|
Sign up to set email alerts
|

The First-aid Advice and Safety Training (FAST) parents programme for the prevention of unintentional injuries in preschool children: a protocol

Abstract: This study will develop the first group-based parenting programme to prevent injuries in preschool children, and design tools for parent-reported injury outcomes. A key challenge will be to recruit parents to participate in a manner that is non-stigmatising, and does not result in feelings of guilt or belief that they are perceived to be a bad parent. The findings will be used to prepare a trial to assess the effectiveness and cost-effectiveness of the intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…[16] As shown in our study, childhood scalding injury is frequently observed among the preschool period, especially between the ages of 2 and 3 years [1][2][3][5][6][7][17][18][19] in which the abilities that increased tendency to injuries were gained such as independent mobility, exploratory behavior, and hand-to-mouth activity. [20,21] Similar to the previous studies from Turkey [23,25] the mechanism of hot milk burns was most commonly the immersion and most frequently affected anatomical parts were the lower extremities and the trunk. Male predominance was demonstrated in our study that in agreement with the previous studies, which had a male to female ratio ranged between 0.9:1 and 2:1.…”
Section: Number Of Patients Mean Burned Bsa (%) Mortality Rate (%)supporting
confidence: 75%
“…[16] As shown in our study, childhood scalding injury is frequently observed among the preschool period, especially between the ages of 2 and 3 years [1][2][3][5][6][7][17][18][19] in which the abilities that increased tendency to injuries were gained such as independent mobility, exploratory behavior, and hand-to-mouth activity. [20,21] Similar to the previous studies from Turkey [23,25] the mechanism of hot milk burns was most commonly the immersion and most frequently affected anatomical parts were the lower extremities and the trunk. Male predominance was demonstrated in our study that in agreement with the previous studies, which had a male to female ratio ranged between 0.9:1 and 2:1.…”
Section: Number Of Patients Mean Burned Bsa (%) Mortality Rate (%)supporting
confidence: 75%
“…The contents of interventions must address falls, fires, poisonings, sleep-related incidents, injuries, and drowning so that parents can create a safe home environment for their children [3,4,[7][8][9][10][11][12][13][14][15][16][24][25][26]. Additionally, parents' awareness of safety accidents involving infants and toddlers that may occur at home must be improved by interventions [3,4,[7][8][9][10][11][12]14,16,18,24,[26][27][28][29]. Finally, interventions should ensure that parents have an accurate knowledge of safety accident prevention for their children…”
Section: Chnrmentioning
confidence: 99%
“…Several Korean and international studies have been conducted in which educational programs on home safety aimed at the parents of infants and toddlers were conducted and analyzed for their effectiveness [4,7,10,11]. Furthermore, many studies on interventions for sleep safety [12][13][14][15], home fire safety accidents [8], first aid [16,17], and car safety accidents [18] have been published, and educational interventions aimed at parents in these studies were confirmed to have a positive effect on the prevention of safety accidents involving children.…”
Section: Introductionmentioning
confidence: 99%
“…The questions related to the cognitive domains (knowledge) were performed before the intervention ( 4 ). Then, the face to face training was conducted for the first group ( 5 ). This training was included the followings: lecture, questioning and answering and self-aid and body-aid educational booklet (prepared and notified by Training Deputy Joint Staff of the IRGC).…”
Section: Dear Editormentioning
confidence: 99%